2017
DOI: 10.1371/journal.pgen.1006637
|View full text |Cite
|
Sign up to set email alerts
|

A genome wide association study identifies a lncRna as risk factor for pathological inflammatory responses in leprosy

Abstract: Leprosy Type-1 Reactions (T1Rs) are pathological inflammatory responses that afflict a sub-group of leprosy patients and result in peripheral nerve damage. Here, we employed a family-based GWAS in 221 families with 229 T1R-affect offspring with stepwise replication to identify risk factors for T1R. We discovered, replicated and validated T1R-specific associations with SNPs located in chromosome region 10p21.2. Combined analysis across the three independent samples resulted in strong evidence of association of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 47 publications
(62 reference statements)
1
34
0
1
Order By: Relevance
“…Acute episodes of T1R are characterized by a cytokine storm which is indicative of dysregulated inflammatory responses. Prospective transcriptomic analyses of the immune response to M. leprae antigen and a genome-wide association study support the central role of host genetics in the break-down of coordinated gene regulation in the T1R phenotype 12,18 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Acute episodes of T1R are characterized by a cytokine storm which is indicative of dysregulated inflammatory responses. Prospective transcriptomic analyses of the immune response to M. leprae antigen and a genome-wide association study support the central role of host genetics in the break-down of coordinated gene regulation in the T1R phenotype 12,18 .…”
Section: Discussionmentioning
confidence: 85%
“…A prospective study of host responses to M. leprae antigen identified a gene-set signature that predisposed to T1R 12 . In addition, candidate gene approaches identified six protein coding genes in association with T1R [13][14][15][16][17][18][19] . More recently a genome-wide association study (GWAS) identified a long noncoding RNA in chromosome 10 as T1R risk factor in independent populations and also provided suggestive evidence for the PRKN (formerly PARK2) as T1R susceptibility gene 18 .…”
mentioning
confidence: 99%
“…Genetic factors have been recognized as an important contributor of leprosy after infected with leprosy bacillus. Genome wide association studies (GWAS) have identified several susceptibility common variants [24,25,26] and lncRNA [27] associated with leprosy. Meanwhile, immune response genes have been proved to be associated with pathogenesis of different forms of leprosy [28] .…”
Section: Discussionmentioning
confidence: 99%
“…The chemokine IP-10 is secreted by various cell types, and through its receptor (CXCR3), it regulates immune responses by activation and recruitment of leukocytes (T cells, monocytes, and NK cells) (10). Leprosy reactions have considerable overlap with acute immunological complications (flares) in other chronic diseases, such as RA (11), Buruli ulcer (12,13), and Crohn's disease (14,15). Flares of these chronic diseases are characterized by a sudden increase in inflammation as well, leading to a deterioration of disease symptoms and often to irreversible tissue damage.…”
mentioning
confidence: 99%